Pengaruh Budaya Organisasi dan Kompensasi terhadap Produktivitas Kerja dengan Kepuasan Kerja sebagai Variabel Intervening - Gina Gayatri; Kartawan Kartawan; Dedi Rudiana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to examine the influence of organizational culture and compensation on work productivity with job satisfaction as an intervening variable. The study was conducted on Puskesmas employees in Tasikmalaya City. Sampling is carried out using techniques of simple random sampling, with a total sample size of 282 samples, spread across 22 Community Health Centers in Tasikmalaya City. The research instrument used is a questionnaire with a likert scale. The analysis technique used is structural equation modeling with the smartPLS application. The results of this research show that 1) Organizational culture and compensation partially have a positive and significant effect on job satisfaction; 2) Organizational culture and compensation partially have a positive and significant influence on work productivity; 3) Job satisfaction is able to act as an intervening variable on the influence of organizational culture and compensation on work productivity